e-Book usage in teaching science: the perspectives of science teachers in secondary schools in Selangor / Kamarol Baharen Mohd Rom … [et al.] - Mohd Rom, Kamarol Baharen; Luaran, Johan@Eddy; Ahmad Nadzri, Fazyudi; Jain, Jasmine (UiTM Press, 2020)
E-book is one of the products of technology that have benefited many educators all around the world. It has also revolutionized the way students learn. Previous studies have shown that e-book brings positive effects on students’ academic achievements. Due to this scenario, this study 1) investigates the preferences of teachers in the use e-book in teaching and learning 2) identifies impacts of using e-book in teaching and learning and 3) determines the challenges of using e-book. 48 science teachers from selected schools in Selangor were the respondents for this study. Quantitative approach was employed with questionnaires used as the instrument. The findings indicated that most of the respondents had positive perceptions on the use of e-book in classrooms and were willing to overcome the challenges that they were facing.